Analysis Of The Business Development Strategy Of The "Lamhot" Staple Food Stalls In Facing Operational Obstacles And Market Competition In Sunggal District, Deli Serdang Regency - Sitorus, Indra Benny; Sari , Dian Septiana (Journal of Management, Economic, and Accounting, 2025)
This study analyzes the development strategy of Lamhot Grocery Stores in facing operational constraints and competition in Sunggal District. Staple food stalls face challenges from modern minimarkets, limited capital, stock management, and transaction recording. This qualitative research uses interviews, observations, and documentation, analyzed with the Miles and Huberman model. Results show strengths in location, customer relationships, and pricing; weaknesses in financial recording and product variations. Opportunities come from stable demand, while threats come from modern retail and changing consumption. Suggested strategies include improving recordkeeping, diversifying products, improving services, digital promotion, and managing working capital to improve business competitiveness.